Gender Role Beliefs and Parents' Support for Athletic Participation. (July 2017) - Heinze, Justin E.; Heinze, Kathryn L.; Davis, Matthew M.; Butchart, Amy T.; Singer, Dianne C.; Clark, Sarah J.
Pay-to-play fees in public schools place more support for sport participation in the hands of parents; this may disproportionately affect the ability of girls to garner the benefits of sports. Using an online survey of a national sample of parents ( N = 814), we examined the relationship between parents' gender role beliefs, parents' beliefs about the benefits and monetary value of sports, and the types of sports their daughters play. The results indicate that parents placed somewhat greater value on sport for sons, than for daughters, both ideologically and financially. Gender role beliefs played a small, but significant role, in shaping parents' beliefs about their daughters' involvement in sport, and the types of sports their daughters play.